Nanocrystalline PbS as Ammonia Gas Sensor: Synthesis and Characterization. Issue 8 (29th June 2015) - Bandyopadhyay, Subhankar; Chatterjee, Bappaditya; Nag, Pooja; Bandyopadhyay, Amitava
<x xml:space="preserve">Abstract</x> This article reports on the synthesis of lead sulfide (PbS) by precipitation at a reaction temperature of 90°C. For its plausible use as ammonia (NH3) gas sensor, the sample was characterized. The X‐ray diffraction results showed that the produced PbS was nanocrystalline with a crystallite size of 33.31 nm. The surface morphology of the sample was studied by scanning electron microscopy. The electrical response of the sample in the form of a thick film was studied in the presence of NH3 and vapors of volatile organic compounds (VOCs) like methanol, ethanol, and isopropyl alcohol within the detection limit of 0–150 ppm at room temperature. The sensing behavior showed that the material synthesized was only influenced by NH3 amongst other gases (VOCs). In addition, the sample exhibited reversible and consistent responses satisfactorily with a relatively short response time (10 s) compared to others. Therefore, it could be used as NH3 gas sensor without the help of any micro‐heater that is traditionally required for existing commercial gas sensors. The gas sensing mechanism is proposed to follow the well‐known Freundlich adsorption isotherm. This isotherm is multi‐molecular, physical, and reversible in nature. Finally, it is suggested that the present findings could be exploited for manufacturing a PbS sensor in a small scale industrial unit.